2010
DOI: 10.1111/j.1463-1318.2009.01779.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of SMAD4 in early‐onset colorectal cancer

Abstract: Objective Chromosomal loss within the region of 18q and loss of SMAD4 expression have been reported to be frequent somatic events during colorectal cancer tumour progression; however, their associations with age at onset have not been widely studied. Method We analysed 109 tumours from a population-based case-family study based on colorectal cancers diagnosed before the age of 45 years. These patients with early-onset colorectal cancer had been previously screened for germ-line mismatch repair gene mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 15 publications
(37 reference statements)
4
14
0
Order By: Relevance
“…This is supported by the methylation data on colorectal cancers of Chinese (Xu et al, 2004) and Japanese origin (Ishiguro et al, 2006). the tumors examined of both Egyptian and Finnish origin consistent with the published literature (Royce et al, 2010;Ahn et al, 2011). SMAD4 is a potential upstream inducer of p15 INK4b (see introduction).…”
Section: Discussionsupporting
confidence: 82%
“…This is supported by the methylation data on colorectal cancers of Chinese (Xu et al, 2004) and Japanese origin (Ishiguro et al, 2006). the tumors examined of both Egyptian and Finnish origin consistent with the published literature (Royce et al, 2010;Ahn et al, 2011). SMAD4 is a potential upstream inducer of p15 INK4b (see introduction).…”
Section: Discussionsupporting
confidence: 82%
“…The results of our study suggest that in colorectal adenocarcinomas, the loss of SMAD4 nuclear expression, [23,[28][29][30][31][32]. In the present study, we investigated a 'homogeneous' group of invasive adenocarcinomas.…”
Section: Discussionmentioning
confidence: 89%
“…Similar to other reported data [28,30], we observed that loss of SMAD4 nuclear expression was infrequent and showed a tendency to relate to aberrant MMR protein expression (p=0.08). However, a complete lack of correlation between SMAD4 expression and presence of microsatellite instability has been reported in early onset colorectal cancer [29] and in inflammatory bowel disease-associated colorectal adenocarcinomas [52]. Events other than abnormal SMAD4 signalling, such as TGFβRII mutation, could be related to abnormal TGFβ signalling in tumours lacking the MMR protein [66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…2,13 Loss of SMAD4 has been reported to occur in 9-67% of CRC and is associated with advanced disease, metastasis and poor prognosis of CRC. 13,[20][21][22][23] It has been proposed that loss of Smad4 may contribute to functional shift of TGF-β from tumor suppressor to tumor promoter. 24,25 Notably, overactivation of TGF-β induced MEK/ERK and p38-MAPK pathways are involved in malignancy promotion and drug resistance of colon cancer.…”
Section: Discussionmentioning
confidence: 99%